The Perilampidae of the United Arab Emirates and Yemen (Hymenoptera: Chalcidoidea) - Darling, D. Christopher; Yoo, Jeong (Zootaxa, 2021)
The family Perilampidae is reported for the first time from the Arabian Peninsula. Krombeinius almokha Darling n. sp. is described from Yemen and seven species of Perilampus Latreille are recorded and illustrated from Yemen and the United Arab Emirates. Two species are recognized in the P. auratus group, Perilampus ardens Yoo & Darling n. sp., P. awbalus Yoo & Darling n. sp., one species in the P. laevifrons/chrysopae group, Perilampus khor Yoo & Darling n. sp., three species in the P. tristis group, Perilampus rainerius (Argaman), 1990, P. houbaraensis Yoo & Darling n. sp., P. yemenensis n. sp., and Perilampus microgastris Ferrière, 1930. The species show primarily Afrotropical and Palaearctic affinities. Comparisons and images are also provided for five extralimital species, P. auratus Panzer, 1798, P. tristis Mayr, 1905, P. chrysonotus Förster, 1859, P. seyrigi Risbec, 1952, and P. noemi Nikol’skaya, 1952, and a lectotype is designated for P. microgastris (present designation). The biogeographic affinities of the Arabian Peninsula Perilampidae are discussed as is “dwarfism” in desert Hymenoptera.